2022
DOI: 10.1109/jeds.2022.3157935
|View full text |Cite
|
Sign up to set email alerts
|

AM Mini-LED Backlight Driving Circuit Using PWM Method With Power-Saving Mechanism

Abstract: This paper proposes a mini-light-emitting diode (mini-LED) driving circuit that is driven by pulse width modulation (PWM) for the backlights of active-matrix (AM) liquid crystal displays (LCDs). The proposed circuit compensates for threshold voltage (VTH) variations of low-temperature polycrystalline silicon thin-film transistors (LTPS TFTs) and the current-resistance (I-R) rise in VSS lines to supply a stable driving current. Operating the mini-LED at the high luminous efficacy by the PWM driving method and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Figure 3 shows two different methods PWM unit and gate node of TCCG is connected. Many other previously proposed analog PWM pixel circuits with a-IGZO TFTs [9], [10], [11], adopted a structure that directly connects PWM unit and gate node of TCCG, or Case 2(figure 3(b)) connection scheme. In the proposed pixel circuit, PWM unit is connected to the gate node of driving TFT of CCG through CCCG, where VTH_CCG is stored instead of gate node of TCCG, like in Case 1(figure 3.(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows two different methods PWM unit and gate node of TCCG is connected. Many other previously proposed analog PWM pixel circuits with a-IGZO TFTs [9], [10], [11], adopted a structure that directly connects PWM unit and gate node of TCCG, or Case 2(figure 3(b)) connection scheme. In the proposed pixel circuit, PWM unit is connected to the gate node of driving TFT of CCG through CCCG, where VTH_CCG is stored instead of gate node of TCCG, like in Case 1(figure 3.(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Deng et al proposed an AM driving circuit using a low-temperature poly-silicon TFT to reduce the power consumption of mini-LED backlight LCD by lowering the drain-source voltage (V DS ) of the switching TFT on the driving current path and reducing the range of required voltage across the proposed circuit [12]. Lin et al reported a mini-LED driving circuit to produce a stable driving current by compensating for the current-resistance rise of the negative voltage of the source (V SS ) and the threshold voltage (V TH ) variation of the driving TFT to reduce the power consumption of the circuit and improve luminous efficiency of mini-LEDs [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the wavelength of μLED's light can shift depending on its current density, resulting in color distortion [8]- [10]. Therefore, pulse width modulation (PWM) driving, which adjusts the emission period with a constant current to express gray levels, must be applied to μLED displays [5], [11]- [14].…”
Section: Introductionmentioning
confidence: 99%